Application of upconversion photoluminescent materials in perovskite solar cells: opportunities and challenges. (September 2021) - Liang, T.; Fu, J.; Li, M.; Li, H.; Hao, Y.; Ma, W.
Abstract: Perovskite solar cells (PSCs) have made remarkable progress and received extensive attention due to their superior photovoltaic performance, making them become the most promising alternative to traditional silicon solar cells. The limitation in solar absorption range remains a roadblock for all photovoltaic devices; at the same time, it is also a prospective approach for further optimization of solar cells by extending the photoabsorption region. Upconversion (UC) materials with rich energy levels could enlarge the spectral absorbance of solar cells from visible to near-infrared by sequentially absorbing two low-energy photons and emitting a high-energy photon. Consequently, application of UC materials in PSCs has been widely researched to minimize the nonabsorption loss and improve the power conversion efficiency of PSCs. However, the low energy transfer efficiency and high-threshold power for UC luminescence remain two huge obstacles to the application of UC materials in PSCs. Herein, we have reviewed the recent research progress in application of UC materials in PSCs concerning how to improve the energy transfer efficiency and reduce the threshold power of UC luminescence, thus enhancing the overall power conversion efficiency of PSCs. Prospects and challenges in utilization of UC materials in PSCs are summarized. Graphical abstract: Image 1